Artificial Intelligence in University Teaching: A Qualitative Analysis from the Faculty Perspective - Elías-Collantes, Maritza Mónica; Palacios-Núñez, Madeleine Lourdes; Toribio López, Alexander (LACCEI, 2025)
Artificial intelligence (AI) is increasingly becoming an integral component in university students’ educational processes. In this context, it is crucial to investigate the challenges, attitudes, and opportunities arising from its pedagogical, technological, and ethical integration, as perceived by educational stakeholders. Therefore, this research aims to analyze university faculty’s perceptions regarding the incorporation of AI into their teaching strategies. To achieve this, a qualitative approach with a phenomenological design was employed. Semi-structured interviews were conducted with ten experienced professors, exploring their levels of familiarity, adoption challenges, attitudes, and professional development needs. Participants identified barriers such as a lack of adequate infrastructure, the financial costs for universities (as not all applications are free), and the need for specialized training. Nevertheless, they acknowledged the potential of these technological innovations to transform teaching practices and strengthen students’ critical skills.